MEMAKNAI WATUGUNUNG DAN OEDIPUS SANG RAJA SEBAGAI MITOS TENTANG WAKTU YANG MELAMPAUI WAKTU - Couteau, Jean (Jurnal Filsafat "WISDOM", 2010)
AbstractIt is very interesting to compare Oedipus and Watugunung myths. Both of them have a similar narrative basic structure. Yet, they are different in meaning. One hand, the myth of Oedipus symbolizes the West anthropocentrism with the â€œ Oedipusâ€ figure as a prototype of West human who is separated from the cosmos, rational, and â€œfreeâ€ but he is undermined by blindness/ blank. In other hand, the myth of Watugunung can be said as one of determiners of Bali/ Java cosmocentrism with the Watugunung figure as a prototype of human who attempts to live in a harmony with the cosmos rhythm. He is not â€œfreeâ€ but he feel enlightened.Thus, â€œblindnessâ€ and â€œenlightenmentâ€, which are presented in the two narratives, are two points which differentiate among point of view of Greek/ West culture and Bali/ Java culture.Keywords: Watugunung myth, Oedipus myth.